The Psychoaggregate System in Human Resource Management - Siemiatowski , Fabian (Studia Oeconomica Posnaniensia, 2014)
This article, through the author’s original approach, identifies and classifies the factors involved in how employees are influenced by their managers. Based on the literature and on research, the author distinguishes the psychoaggregates system in management. This system consists of psychostimulation and psychomanipulation factors. The identification of the two groups of psychoaggregate system variables made it possible to construct a model that can be used to analyse organizations in terms of the dominant factors of exerting influence, and an evaluation of the results of these analyses can determine the nature of an organization in the context of the relations between managers and employees.